Severe acute respiratory syndrome coronavirus 2 RNA contamination of inanimate surfaces and virus viability in a health care emergency unit. (August 2020) - ,; Bruno, R.; Mondelli, M.U.; Brunetti, E.; Di Matteo, A.; Seminari, E.; Maiocchi, L.; Zuccaro, V.; Pagnucco, L.; Ludovisi, S.; Lissandrin, R.; Parisi, A.; et al.
Abstract: Objectives: To detect possible severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) RNA contamination of inanimate surfaces in areas at high risk of aerosol formation by patients with coronavirus disease 2019 (COVID-19). Methods: Sampling was performed in the emergency unit and the sub-intensive care ward. SARS-CoV-2 RNA was extracted from swabbed surfaces and objects and subjected to real-time RT-PCR targeting RNA-dependent RNA polymerase and E genes. Virus isolation from positive samples was attempted in vitro on Vero E6 cells. Results: Twenty-six samples were collected and only two were positive for low-level SARS-CoV-2 RNA, both collected on the external surface of continuous positive airway pressure helmets. All transport media were inoculated onto susceptible cells, but none induced a cytopathic effect on day 7 of culture. Conclusions: Even though daily contact with inanimate surfaces and patient fomites in contaminated areas may be a medium of infection, our data obtained in real-life conditions suggest that it might be less extensive than hitherto recognized.